Determination of Active Ingredients in Pesticide Formulations by Gas Chromatography with an Electron Capture Detector - Chai Mee, Kin; Tan Guan, Huat; Asha, Kumari (Malaysian Journal of Science, 2005)
A fast, reliable and effective method for direct determination of two active ingredients namely Chlorpyrifos, and Quinalphos in two pesticide formulations has been established by using Gas Chromatography - Electron Capture Detector (GC-ECD) with the internal standard method. A pure standard solution spiked with internal standard in methanol was sonicated to homogenise the solutions. 2 µL volume of a standard solution was injected. A six point calibration curve that demonstrated a linear range was established for each target compound. The concentration of active ingredients in pesticide formulations was calculated from peak area values at a retention time interpolated in a calibration graph was prepared. Analytical results obtained 36.91 ± 0.52 % of Chlorpyrifos and 10.59 ± 1.07 % of Quilnalphos were within specification for both commercial pesticide formulations.